β-Hydroxyisovalerylshikonin regulates macrophage polarization via the AMPK/Nrf2 pathway and ameliorates sepsis in mice - Tao Pan; Yabin Chang; Min He; Zehui He; Jun Jiang; Xinling Ren; Fang Zhang (Taylor & Francis Group, 2022)
Context The potential anti-inflammatory bioactivities of β-hydroxyisovalerylshikonin (β-HIVS) remain largely unknown.Objective This study investigated the anti-inflammatory effects and underlying mechanisms of β-HIVS.Materials and methods RAW 264.7 cells stimulated with LPS (100 ng/mL) for 24 h were treated with the non-cytotoxic doses of β-HIVS (0.5 or 1 μM, determined by MTT and Trypan blue staining), qRT-PCR and FCM assay were used to examine macrophage polarization transitions. Western blotting was used to evaluate the activation of the AMPK/Nrf2 pathway. In vivo, C57BL/6 mice were randomly divided into vehicle control, LPS (10 mg/kg), and β-HIVS (2.5 mg/kg) combined with LPS (10 mg/kg) groups, blood samples, BALF, and lung tissues of mice were subjected to ELISA, qRT-PCR, FCM, and H&E staining.Results β-HIVS (1 μM) inhibited LPS-induced expression of M1 macrophage markers (TNF-α: 0.29-fold, IL-1β: 0.32-fold), promoted the expression of M2 macrophage markers (CD206: 3.14-fold, Arginase-1: 3.98-fold) in RAW 264.7 cells; mechanistic studies showed that β-HIVS increased the expression of nuclear Nrf2 (2.04-fold) and p-AMPK (3.65-fold) compared with LPS group (p < 0.05). In vivo, β-HIVS decreased the levels of pro-inflammatory cytokines (TNF-α: 1130.41 vs. 334.88 pg/mL, IL-1β: 601.89 vs. 258.21 pg/mL in serum; TNF-α: 893.07 vs. 418.21 pg/mL, IL-1β: 475.22 vs. 298.54 pg/mL in BALF), decreased the proportion of M1 macrophages (77.83 vs. 68.53%) and increased the proportion of M2 macrophages (13.55 vs. 19.56%) in BALF, and reduced lung tissue damage and septic mice survival (p < 0.05).Conclusions These results indicate that β-HIVS may be a new potential anti-inflammatory agent.